RIAU MALAY ETHNOPARENTING ON CHILDREN AGED 4-6 YEARS IN THE BUKIT PAYUNG TRANSMIGRATION AREA IN KAMPAR - Farah Nurhaliza; Ria Novianti; Defni Satria (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
This paper discusses activities related to parenting that are closely interconnected with culture and are described from the perspective of indigenous communities. The research employs a qualitative approach using ethnographic methods. Data were collected through in-depth interviews and subsequently analyzed using the coding technique with NVivo 12.2 software. The findings show that Malay ethnoparenting based on Tunjuk Ajar Melayu through the “Twenty-Five Principles” practiced by parents in Bukit Payung Village has a significant influence on children’s socialization with people around them and with the environment in which they live. Parenting practices applied by families of different ethnic backgrounds show variations across households. Nevertheless, the study identifies similarities in the core values embedded in parenting, which function as fundamental principles in the child-rearing process. The results further reveal that Riau Malay ethnoparenting implemented in the transmigration area of Bukit Payung Village prioritizes religious values as a primary foundation, along with tolerance for differences, humility toward others, integrity and courage, and the provision of space for the social environment to contribute to the formation of children’s cultural identity.